(untitled) (Scientific journal of the Fergana State University, 2023)
This article reflects the relations of Uzbek and Tatar enlighteners in Turkestan in the second half of the XIX century - the first quarter of the XX century. It is said that the Tatar enlighteners initiated the creation of Russian literature, technology, theater, newspapers and magazines in Turkestan and carried out their activities in cooperation with the Uzbek enlightenment